Morphophysiology and production of cotton irrigated with saline waters and fertilized with nitrogen - dos Santos, João Batista; Gheyi, Hans Raj; de Lima, Geovani Soares; Xavier, Diego Azevedo; Cavalcante, Lourival Ferreira; Marenco Centeno, Cruz Ramón (Comunicata Scientiae, 2016)
The high salt concentrations found in irrigation formation of water in semi-arid regions lead to changes on crops growth and development and can lead to halomorphicsoils formation. In this context, it was proposed to evaluate the morphophysiology and production of colored herbaceous cotton BRS Topaz fertilized with nitrogen under a saline-sodic soil and submitted to the irrigation with water of different salinities. The experiment was conducted in an eutrophic sandy quartzarênico Neossol in the municipality of Campina Grande, Paraíba, Brazil, adopting a completely randomized design in 5x5 factorial with three repetitions, with five salinity levels of the the irrigation water (0 7; 2.7; 4.7; 6.7 and 8.7 dS m-1 at 25°C) and five levels of nitrogen (40; 60; 80; 100 and 120 mg of N kg-1). Regarding cotton growth, no effect was observed for the interaction between salinity and soil nitrogen doses. The absolute growth rate for height, stem diameter and leaf area decreased with an increase in the irrigation water electrical conductivity, being leaf area the most affected variable.The number of bolls and the cotton seed production per plant decreased with the salinity increase and increased with in increase of nitrogen fertilization.